2021
DOI: 10.3389/fsurg.2021.771026
|View full text |Cite
|
Sign up to set email alerts
|

Pure Laparoscopic vs. Open Right Hepatectomy in Living Liver Donors: Bench-Surgery Time

Abstract: Background: Recently, there have been several reports on pure laparoscopic donor right hepatectomy (PLDRH), but the effect of pure laparoscopy on bench surgery has not been evaluated. This study aimed to compare bench-surgery time between PLDRH and conventional donor right hepatectomy (CDRH).Methods: We retrospectively reviewed the medical records of 758 live liver donors between January 2012 and December 2019. We divided the patients into two groups: between January 2012 and September 2015, when we exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The CDRHM group had a significantly shorter bench time than the PLDRHM group. This finding is consistent with our previous study, which, although limited to right donor hepatectomies without MHV inclusion, reported longer bench times in PLDH hepatectomies than in conventional open donor hepatectomies [ 19 ]. We believe that this finding can be attributed to shorter vasculature and bile duct length in the laparoscopically harvested liver grafts as a result of instruments such as clips and staplers, thus requiring longer bench times to improve the graft quality.…”
Section: Discussionsupporting
confidence: 93%
“…The CDRHM group had a significantly shorter bench time than the PLDRHM group. This finding is consistent with our previous study, which, although limited to right donor hepatectomies without MHV inclusion, reported longer bench times in PLDH hepatectomies than in conventional open donor hepatectomies [ 19 ]. We believe that this finding can be attributed to shorter vasculature and bile duct length in the laparoscopically harvested liver grafts as a result of instruments such as clips and staplers, thus requiring longer bench times to improve the graft quality.…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies have primarily emphasized donor, rather than recipient, outcomes. Moreover, our previous study indicated the potential for a higher incidence of recipient complications and lower graft quality associated with PLDRH compared with CDRH 7 , 16 , 33 . Although we did not establish any absolute contraindications, we followed a policy that considered donor age and informed donors and their families about the potential for a higher rate of recipient complications in PLDRH compared with CDRH.…”
Section: Discussionmentioning
confidence: 96%
“…This highlights the need for heightened caution during PLDRH procedures. To ensure sufficient remnant liver volume, there may be a tendency to position the transection plane toward the graft side, potentially resulting in a poor-quality liver graft cut surface 33 . This effect can be particularly pronounced when dealing with a limited optimal vascular or bile duct division space.…”
Section: Discussionmentioning
confidence: 99%
“…The need for additional trimming or bench-surgery procedures to ensure graft quality can significantly impact the duration of bench surgery. We revealed that the bench surgery duration was lengthier in the PLDRH group when compared to the open group, irrespective of whether the vascular network was reconstructed ( 45 ). Additionally, the estimated graft weight did not differ significantly between PLDRH and open donor right hepatectomy.…”
Section: Discussionmentioning
confidence: 99%